A smartphone-based sensor for detection of iron and potassium in food and beverage samples - Kul, Seyda Mihriban; Chailapakul, Orawon; Sagdic, Osman; Ozer, Tugba (ELSEVIER SCI LTD, 2024)
A novel approach for simultaneous detection of iron and potassium via a smartphone-based potentiometric method is proposed in this study. The screen printed electrodes were modified with carbon black nanomaterial and ion selective membrane including zinc (II) phtalocyanine as the ionophore. The developed Fe 3+ -selective electrode and K + -selective electrode exhibited detection limits of 1.0 x 10 -6 M and 1.0 x 10 -5 M for Fe 3+ and K + ions, respectively. The electrodes were used to simultaneously detect Fe 3+ and K + ions in apple juice, skim milk, soybean and coconut water samples with recovery values between 90% -100.5%, and validated against inductively coupled plasma-optical emission spectrometry. Due to the advantageous characteristics of the sensors and the portability of Near Field Communication potentiometer supported with a smartphone application, the proposed method offers sensitive and selective detection of iron and potassium ions in food and beverage samples at the point of need.
Keywords: Electrochemical sensor; Carbon black; Food; Potentiometric ion selective electrode; Phthalocyanine; Near field communication; ION-SELECTIVE ELECTRODES; MEMBRANE; PERFORMANCE; SURFACE; Chemistry; Food Science & Technology; Nutrition & Dietetics